Non-destructive Testing of a 100-Year-Old Reinforced Concrete Flat Slab Bridge - Wolert, Patryk J.; Kolodziejczyk, Marek K.; Stallings, J. Michael; Nowak, Andrzej S. (Frontiers in Built Environment, 2020)
Non-destructive tests and field measurements were used to establish the structural details and behavior of a 100-year-old reinforced concrete flat slab bridge. There are no structural drawings of the bridge, its reinforcing details, or records from the time of its original construction. The purpose of this project was to identify the structural details necessary to model the bridge for a determination of its ultimate load capacity. This paper discusses the methods used to accomplish this purpose. Live load tests were performed to investigate the overall behavior of the bridge. A finite element model of a single span of the 11-span bridge was developed in ABAQUS. FE model calibration was performed based on measured strains and deflections. Comparison of the finite element analysis and live load test results are presented herein.